Stethoscope hygiene: A call to action. Recommendations to update the CDC guidelines. (19th June 2021) - Kalra, Sarathi; Amin, Alpesh; Albert, Nancy; Cadwell, Cindy; Edmonson, Cole; Gaynes, Robert; Hand, Mary; Marinella, Mark; Morely, Colleen; Sieck, Sandra; Vasudevan, Rajiv S.
Abstract: Healthcare-acquired infections are a tremendous challenge to the US medical system. Stethoscopes touch many patients, but current guidance from the Centers for Disease Control and Prevention does not support disinfection between each patient. Stethoscopes are rarely disinfected between patients by healthcare providers. When cultured, even after disinfection, stethoscopes have high rates of pathogen contamination, identical to that of unwashed hands. The consequence of these practices may bode poorly in the coronavirus 2019 disease (COVID-19) pandemic. Alternatively, the CDC recommends the use of disposable stethoscopes. However, these instruments have poor acoustic properties, and misdiagnoses have been documented. They may also serve as pathogen vectors among staff sharing them. Disposable aseptic stethoscope diaphragm barriers can provide increased safety without sacrificing stethoscope function. We recommend that the CDC consider the research regarding stethoscope hygiene and effective solutions to contemporize this guidance and elevate stethoscope hygiene to that of the hands, by requiring stethoscope disinfection or change of disposable barrier between every patient encounter.